Successional changes in the morphology and ecological responses of a grazed pasture ecosystem in Central Spain (Plant Ecology, 1986)
Morphological characteristics related to spatial occupation, reproduction and adaptations to grazing were used to characterize the most frequent species in a therophytic pastureland of Central Spain. Periodic ploughing is a traditional practice in these pastures and allows observation of successional change. In the present study, four neighbouring slopes of differing time since last ploughing were chosen. Species biomass was measured at different times during the annual growing season for two different slope positions. Grazing pressure is an important environmental factor affecting ecosystem organization, the most palata- ble plants tending to show increasing biomass with succession. In the most mature stages, there is a predomi- nance of species characterized by horizontal occupation of space and sprouting after mowing or grazing. During succession segregation of the different morphological characteristics occurs in slope sectors related to geomorphological dynamics. Similarly, phenological development tends to be later in pastures in the lowest slope zones, due probably to their greater summer soil moisture content.